Flexibility: The next competitive battle the manufacturing futures survey - Meyer, Arnoud De; Nakane, Jinichiro; Miller, Jeffrey G.; Ferdows, Kasra (Strategic Management Journal, 1989)
Abstract Over the past 4 years research teams from INSEAD (Fontainebleau), Boston University and Waseda University (Tokyo) have administered a yearly survey on the manufacturing strategy of the large manufacturers of the three industrialized regions of the world. In this paper the results for the 1986 survey are compared. One of the most striking results of that year's survey is the emphasis some of the more advanced manufacturers put on their efforts to overcome the trade‐off between flexibility and cost efficiency. In particular for the Japanese respondents these attempts become clear. Europeans and North Americans are not yet seizing the opportunity to cut costs through rapid production and design changes, and are focusing more on traditional cost reduction programmes and the improvement of quality. This might mean that they are preparing the basis on which they can built to obtain added value from flexible automation. If this is the case then the Japanese are clearly ahead.